HUBUNGAN PENGETAHUAN K3 HASIL BELAJAR SISWA KELAS XI DAN XII JURUSAN TEKNIK PEMESINAN SMK PEMBANGUNAN BUKITTINGGI” - Abdul Rahim Shiddiq; Jasman Jasman; Budi Syahri; Bulkia Rahim (Jurnal Vokasi Mekanika (VoMek), 2024)
Implementing Occupational Safety and Health (OSH) is a way to prevent occupational hazards. Initial observations showed that students did not follow the OHS guidelines. This problem is suspicious because SMK has not established safety measures in the workplace. Students still do not understand OHS, so it requires development so that the application of work safety can adjusted to normal demands of industry. If this is left unchecked, SMK graduates will become less capable. The Destination of occupational safety and health is to establish a prosperous, safe, and healthy work environment and society. With OHS, a workforce that is free from accidents and has good physical, mental and social health will create a safe working environment. The purpose of implementing OSH is very important to maximise the results achieved because it ensures the safety and security of workers, as well as the security of facilities and infrastructure, and prevents accidents. This study found a significant relationship between OHS knowledge and student learning outcomes, as evidenced by the test results. Twenty students from grades XI and XII in the Mechanical Engineering Department participated in this study during January - June 2023/2024. The value showed a Substansial relationship between OHS knowledge and student performance at SMK Pembangunan Bukittinggi. This was confirmed by the regression test results, with an R value > 0.657 which R table value of 0.444, thus supporting the research hypothesis.